Bahumukhī - Meśrāma, Keśava, 1937- (Kolhāpūra : Pracāra Prakāśana : Pramukha vitaraka Siddhārtha Buka Seṇṭara, 1984)
Articles on Dalit movement and literature.
In Marathi.
Mode of access: Internet.
Keywords: Indic literature -- Untouchable authors -- History and criticism; Dalits -- India -- Politics and government